2018
DOI: 10.1111/bjd.17149
|View full text |Cite
|
Sign up to set email alerts
|

Benefit–risk profile of tofacitinib in patients with moderate‐to‐severe chronic plaque psoriasis: pooled analysis across six clinical trials

Abstract: Tofacitinib has a benefit-risk profile in moderate-to-severe psoriasis consistent with that of other systemic treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
0
20
0
5
Order By: Relevance
“…On the other hand, perifollicular repigmentation was observed in the patient's vitiligo patches in response to tofacitinib. A possible explanation could be that concomitant tofacitinib and NB‐UVB act synergistically, which is supported by studies that have shown that JAK inhibitors are more effective when combined with phototherapy …”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, perifollicular repigmentation was observed in the patient's vitiligo patches in response to tofacitinib. A possible explanation could be that concomitant tofacitinib and NB‐UVB act synergistically, which is supported by studies that have shown that JAK inhibitors are more effective when combined with phototherapy …”
Section: Discussionmentioning
confidence: 94%
“…Also, an investigation of the effects of tofacitinib on the viral loads of Cytomegalovirus and Epstein-Barr virus pointed to no clinically significant effects of this JAK inhibitor [31]. The risk of infection during treatment with tofacitinib seems to be similar to that during treatment with biologics [6,9], and the overall benefit/risk profile of the drug when used for psoriasis appears to be comparable to those of other systemic treatments [32].…”
Section: Discussionmentioning
confidence: 98%
“…Safety profile is considered generally acceptable, infections and laboratory abnormalities can be observed as major adverse events (226). The increased risk of infections was similar to that observed by the use of biologics, with the exception of higher risk for varicella zoster infection which should be taken into consideration.…”
Section: Adverse Events During Jak Inhibitor Treatment In Inflammatormentioning
confidence: 99%